FIGURATIVE MEANING FOUND IN QUEEN’S ALBUM - Kadek Bagus Rusmana; I Nyoman Kardana; I Gusti Ngurah Adi Rajistha (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The phenomenon of miss interpretation and the mismatch of the desired meaning in a song's lyrics results in the wrong use of the song in an event. This study discusses the types of figurative meaning and their meaning related to each type. The data of this study were taken from the song lyrics of Queen’s album. Data were collected by analyzing base on the theoretical concepts and the data were analyzed using the observation method. Data were obtained from listening and reading the song lyrics repeatedly. Based on the result of the analysis, it was found that there are nine types of figurative meaning that are used in twelve songs from Queen’s Album. The figurative meaning that are used are metaphor, metonymy, overstatement/hyperbole, paradox, simile, symbol, synecdoche, euphemism, and idiom. Metaphor, metonymy, overstatement/hyperbole, simile, symbol, and idiom are the dominant type appeared the most with each 5 data, following by euphemism with 4 data, and the last are paradox and synecdoche with each 1 data. Thus, the total of all the data are 36 of the figurative meaning found in Queen’s album. Metaphor, metonymy, overstatement/hyperbole, simile, symbol, and idiom are the dominant typed found in the song lyric because Queen’s mostly uses substitutes and imagery in their songs.